THE METHODS OF IMPROVING VOCABULARY IN LEARNING FOREIGN LANGUAGES - Quvvatova Shodiya O’ktam qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
In this article, we discuss the benefits of expanding your vocabulary, outline how to improve your vocabulary in English and offer tips for remembering new words. The English language is continually evolving, which gives you the chance to expand and improve your vocabulary. Learning how to increase your knowledge of English can help you both at school and in a professional setting. A greater vocabulary can boost your ability to share your thoughts and ideas and better understand what others are trying to communicate to you.